Tecniques to foster cooperative learning in english as foreign language classrooms, benefits and drawbacks - Avila Espino, José Guillermo; Hernández Menjívar, Jorge Adolfo; Recinos Abarca, Abraham (2024)
The learning of languages is nowadays necessary not only in developed countries but also in underdeveloped countries like El Salvador because it has been extended around the world. These times even the farthest or poorest countries are in contact with English. Countries around the world get to be known by other people, races and cultures. Languages, especially English, have become a very important tool for countries to communicate with one another. English as one of the most spoken languages on Earth becomes a universal language each day. Universities around the world include languages learning, particularly English, in undergraduate and posgraduate programs; and the University of El Salvador (UES) is not the exception. Nowadays, studying a foreign language, especially English has become a necessity in El Salvador, since English is the language being used around the world regarding technology, medicine, commerce and the like. Many students at the University of El Salvador (UES) choose English as their major with the hope of being more competitive and prepared when looking for a job. For this reason the School of Arts and Sciences by means of the Foreign Language Department (FLD) which has the major in English Teaching whose demand increases every year, has the compromise of giving its students the best education in the teaching and learning of the English language. To accomplish this, the Foreign Language Department has to make use of different teaching techniques which help students to learn English in the best possible way. Something that has to be remarked is that students of all levels learn a foreign language in a better way when they are provided ample opportunities in the classroom to attain a foreign language. Cooperative Learning is considered by many teachers and researchers as a successful strategy in the teaching of the English as a Foreign Language in which small and even large groups, each with students of different levels of ability, use a variety of learning activities to improve their understanding of a subject. These teaching techniques have an important impact on the opportunities for success for every student at the Department.This research is focused on those techniques that foster cooperative learning in English as foreign language classrooms. Based on the readings of many professionals that have written concerning this topic and the different researches that have taken place all along history proving it effectiveness, these, together with the personal experience as students, we can assure that cooperative learning techniques are important tools for teachers and students who want to get the best out of their English lessons. Also, knowing the typical environment of the English classrooms at the FLD (crowded classrooms), again, it is highly recommended to pay attention to this research. Through this work the reader will find the objectives who led the research and the justification which clarifies why the topic and the research were chosen. Also, the essay which contrasts the benefits and drawbacks of the cooperative learning and the techniques to be applied in the classroom. On the other hand the reader will find the methodology followed to accomplish the research. Besides, the surveys and the interviews administered to students and professors of the Foreign Language Department of the University of El Salvador to enrich the research will be found out.